Perbandingan keanekaragaman spesies dan kelimpahan arthropoda predator penghuni tanah di sawah lebak yang diaplikasi dan tanpa aplikasi insektisida - Siti Herlinda; Waluyo Waluyo; S. P. Estuningsih; Chandra Irsan (Perhimpunan Entomologi Indonesia, 2008)
Studies on soil-dwelling predatory arthropods were carried out in lowland areas of South Sumatra, with objectives to analyze the species diversity and abundance of the predatoryarthropods inhabiting fields applied by synthetic insecticide, bioinsecticide, and without insecticide application. The predatory arthropods were sampled using pitfall traps. Indices of diversity and community similarities were applied to analyze the data. Results indicated that the arthropods inhabiting field without insecticide application had the highest diversity and abundance compared to other treatments. Predatory community similarities between those on the field without insecticide application and applied by bioinsecticide were higher compared to the fields applied by synthetic insecticide.